Analisis Bibliometrik: Tren Penelitian Sustainability Accounting pada Database Scopus (2015-2024) - Reyhan Dzikriansyah Sunarno; Sri Ningsih (Owner : Riset dan Jurnal Akuntansi, 2025)
This study aims to analyze research trends in the field of Sustainability Accounting published in the Scopus database between 2015 and 2024. The method used is bibliometric analysis with the help of VOSViewer software. Of the total 406 articles found, 63 articles relevant to this topic were selected based on certain criteria, reducing the number of remaining articles by 84.5%. The results of the analysis using Overlay Visualization (Co-occurrence) show that sustainability accounting is the center of research that is closely related to sustainability reporting, environmental accounting, and sustainability management. The development of research from 2015 to 2024 began with a focus on basic concepts, then shifted to sustainability integration and deepened on climate change issues and carbon accounting. Network Visualization reveals the close relationship between concepts with the formation of certain topic clusters. Density Visualization shows that the main topics have been widely studied, while carbon disclosure and circular economy are still in the exploration stage. Limitations of this study include the reliance on data from Scopus which may not cover all relevant publications, and the selected timeframe (2015-2024) which may limit understanding of long-term trends. Future research is recommended to explore topics such as gas emissions and climate risk disclosures as they relate to environmental risk management and sustainability implementation, especially in developing countries.